The Geographies of International Student Mobility: Spaces, Places and Decision-Making - Yu, Jing (Journal of International Students, 2020)
The Geographies of International Student Mobility: Spaces, Places and Decision-Making is a timely volume offering distinctive and critical insights into the geographical dimensions of international student mobilities. After the 2016 United Kingdom referendum to leave the European Union, and in the same year, the election of Donald Trump as the President of the United States, both countries faced the rise of conservative populism and sociopolitical upheavals. Brexit and Trumpism have been reshaping the politics of Western democracies in a more nationalistic and nativist way. This anti-immigration macro-level trend actually has ramifications for the internationalization processes of UK higher education.